Surgical outcomes after single event multilevel surgery in cerebral palsy patients with mid-stance knee hyperextension - Chung, Chin Youb; Kwon, Soon Sun; Park, Moon Seok; Lee, Kyoung Min; Sung, Ki Hyuk (Gait and Posture, 2020)
Background: Some patients with cerebral palsy (CP) exhibit excessive knee flexion at initial contact followed by knee hyperextension (KE) in mid-stance. Research question: This study investigated the change in sagittal kinematics after distal hamstring lengthening (DHL) and triceps surae lengthening procedures in CP patients with KE, and compared it to those without KE. In addition, the risk factors for the worsening of postoperative KE were analyzed. Methods: Consecutive 312 patients (596 limbs) with CP who underwent DHL and triceps surae lengthening were included. All patients underwent preoperative and 1-year postoperative three-dimensional gait analysis. Patients’ limbs were divided into the KE and knee flexion (KF) groups, according to preoperative minimum knee flexion in stance. KE was defined as minimum knee flexion in stance less than 0°. Results: The KE and KF groups included 130 and 466 limbs, respectively. Knee and ankle sagittal kinematics significantly improved after surgery in both groups. Minimum knee flexion in stance significantly increased from -6.6˚ to 0.5˚ in the KE group, but decreased from 14.6˚ to 7.8˚ in the KF group. Among the KE group, minimum knee flexion in stance improved in 103 limbs (79.2 %), but worsened in 27 limbs (20.8 %). Degree of preoperative KE was the only factor significantly associated with postoperative worsening of KE (p=0.002). The cutoff value for the worsening of KE was -5.8˚ of preoperative minimum knee flexion in stance. Significance: This study demonstrated that the sagittal kinematics of the knee and ankle joints improved after DHL and triceps surae lengthening procedures in CP patients with and without KE. Preoperative degree of KE was a risk factor for the worsening of KE after surgery. Therefore, careful selection for indication of DHL is required to prevent postoperative KE due to overlengthening of the hamstrings, particularly in patients with severe preoperative KE.
Keywords: Adolescent; Ankle Joint; Biomechanical Phenomena; Cerebral Palsy; Child; Child, Preschool; Female; Gait Analysis; Hamstring Muscles; Humans; Knee Joint; Male; Muscle, Skeletal; Postoperative Period; Retrospective Studies; Standing Position; Tenotomy; Treatment Outcome; Cerebral palsy; Distal hamstring lengthening; Knee hyperextension; triceps surae lengthening